The reification of structural violence in video games. (March 2021) - Denham, Jack; Hirschler, Steven; Spokes, Matthew
The Grand Theft Auto franchise features prominently within existing research exploring graphic, virtual, lawless, and damagingly realistic interpersonal violence within video games. Following a review of this literature, we empirically interrogate notions of the 'realistic' and the 'violent' during gameplay, finding that the undertones of systemic, structural, capitalistic violence are experienced by players as providing the gritty sense of the 'real' that the game has been criticised for. Using Galtung's concept of 'structural violence' and Žižek's notion of the 'real', we unpack structural violence as the forerunning violent experience in the open world game. Due to the hidden and subdued nature of this violence, often taken for granted and experienced passively, we argue that it is the most impactful player experience that simultaneously makes the game playable and contextualises violent game activities. For cultural criminology, our data suggest that embedded and discrete forms of violence should be the leading edge of concern when studying the digital economy and playable forms of social harm.